Correlation Between Knowledge and Attitudes of Mothers with The Fulfillment of Toddler's Health Services During The Covid-19 Pandemic - Laila Ramadani Putri (Media Gizi Kesmas, 2022)
Background: The world is currently facing the spread of a new corona-virus called COVID-19 and designated as a global pandemic. This pandemic condition has forced several community health services to be stopped, including Posyandu. This has resulted in a decrease in immunization coverage and vitamin A administration for toddlers.Objectives: This study aimed to analyze the correlation between knowledge and attitudes of mothers with the fulfillment of toddler's health services during the COVID-19 pandemic.Methods: This research was an online survey conducted in the East Java region. This research was an observational study with a cross-sectional study design. The sample used was 80 people who had returned the questionnaire. Data collection was done online by using Google form that distributed within one week. Data analysis performed using the chi-square test.Results: The results showed that most of the respondents had good knowledge (78,3%) and positive attitudes (92,5%). Based on this research, it can be seen that there was correlation between knowledge (p value = 0,000) and attitudes of mothers (p value = 0,007) with the fulfillment of toddler's health services during the COVID-19 pandemic.Conclusions: There is correlation between knowledge and attitudes of mothers with the fulfillment of toddler's health services during the COVID-19 pandemic. It is necessary to increase health promotion to prevent the emergence of diseases that can be prevented by Immunization (PD3I) and contracting Covid-19.